Penyuluhan Membangun Kesadaran Hukum Gen-Z tentang Ancaman Judi Online - Kadir, Syukron Abdul; Rahmat, Noor; Artha, Bhenu; Kaya, Axcell Ezhalio Melvin; Putri, Wulan Julianti (Yayasan Pondok Pesantren Sunan Bonang Tuban, 2025)
This community service aims to provide the audience with an understanding of the phenomenon of online gambling, the legal basis, and the legal consequences of online gambling. This activity was carried out in Dukuh Hamlet RT.05, Seloharjo Village, Pundong District, Bantul Regency, in August, 3rd 2025with a target audience of 25 people using the counseling method. Knowledge about the phenomenon of online gambling, the legal basis, and the legal consequences of online gambling began to be understood by the participants, seen from the great enthusiasm to understand about these matters. Participants have understood the material presented.